International Reserves: The Experience of Ukraine and Poland - Harkusha Yuliya O. (Bìznes Inform, 2023)
The article highlights the theoretical and practical foundations of management of international reserves of both Ukraine and Poland. The article characterizes the system of elements of management of international reserves of the National Bank of Ukraine, which include: goals and principles of management; organizational structure of management; risks of operations with international reserves; risk assessment. The stages of management of international reserves of the National Bank of Poland are allocated and characterized, the relevant structures are defined. It is noted that in the process of managing foreign exchange reserves in Poland, decisions are made and implemented directly by the central bank of the country, without the participation of external asset managing institutions. The investment process is based on guidelines approved by the Board of the National Bank of Poland, including a set of norms, regulations and procedures, in particular on the decision-making process, permissible asset classes, as well as rules for financial risk management, including the establishment of credit limits and criteria for selecting a contractor. The structure of international reserves of both the National Bank of Ukraine and the National Bank of Poland is analyzed in terms of currencies. The value of gold and the share of gold in the international reserves of the National Bank of Ukraine and the National Bank of Poland are evaluated in dynamics. On the basis of the carried out study, conclusions were drawn and concrete proposals were formulated for improving the process of managing international reserves, taking into account international experience, namely: to optimize the structure of international reserves by diversifying it and expanding the list of reserve currencies; to increase the share of monetary gold as a reliable asset; to expand the direction of investing international reserves, in particular, to consider the possibility of investing in securities of countries that demonstrate sustainable development of their economies.